STRATEGI DINAS KOPERASI DAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) DALAM MENINGKATKAN KUALITAS USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI KOTA PEKANBARU TAHUN 2018 - Osvaldo Elia Sibarani; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Pekanbaru City itself is one of the cities in Riau Province which has a relatively large number of Micro, Small and Medium Enterprises. Pekanbaru City itself, which is the capital of Riau Province, has made a lot of business efforts from the community to stand in this city and also economic activity is more prevalent in this city because of its position as the capital city in Riau Province. However, in reality the number of businesses in Pekanbaru City is not in line with the quality of their business. Therefore it is necessary to have a strategy from the Department of Cooperatives and UMKM in Pekanbaru City in improving the quality of umkm in the city of Pekanbaru.               This study aims to find out how the strategy of the cooperative and umkm service in Pekanbaru City in improving the quality of MSMEs in Pekanbaru City in 2018 and to find out what are the inhibiting factors in implementing the strategy for improving the quality of UMKM in Pekanbaru City in 2018. This study uses a qualitative approach with descriptive methods. In this study the authors used interview and documentation techniques and conducted research at the Department of Cooperatives and UMKM in Pekanbaru City.This study uses 3 types of strategies proposed by Hadari Nawawi, including aggressive strategies, innovative strategies, and diversification strategies. The results of this study are the strategies of the KotaPekanbaru Cooperative and UMKM Department in improving the quality of business in 2018, but in its implementation there are still some Obstacles both in terms of business actors as objects of empowerment and the government itself as an agency that improves quality besides that in this study, it is also explained that the inhibiting factors that affect the Department of Cooperatives and MSMEs in implementing the strategy to improve the quality of MSMEs in Pekanbaru City in 2018 include the large number of umkm made the Pekanbaru City Cooperative and UMKM Office prioritize business actors who have IUMK, lack of experts in business consulting clinics, implementation of bazaars and promotion of business products whose participants are still limited, increase in umkm every year while the number of ah sdm, doing empowerment is still still there, there are still business actors who do not know the empowerment being carried out and the product is still not able to competeKeyword: UMKM, Strategy, Improve Quality.